Therapy of thyroid carcinoma with the histone deacetylase inhibitor MS-275 - Altmann, Annette; Eisenhut, Michael; Bauder-Wüst, Ulrike; Markert, Annette; Askoxylakis, Vasileios; Hess-Stumpp, Holger; Haberkorn, Uwe (European journal of nuclear medicine and molecular imaging, 2010)
Purpose: Dysregulation of histone acetylation associated with an up-regulation of histone deacetylase (HDAC) activity is common in malignant tumours. Therefore, HDAC inhibitors were developed whose effects on proliferation and apoptosis have been shown in different tumour entities. Since non-iodide-concentrating thyroid carcinomas represent a therapeutic problem, this study addressed the effects of the HDAC inhibitor MS-275 on thyroid carcinoma cells. Methods: After the antiproliferative effect of MS-275 had been proven in different human and rat thyroid carcinoma cell lines, FRO82-2, SW1736 and FTC133 cells were further investigated with respect to changes in apoptosis, cell cycle and metabolism by the annexin V/propidium iodide assay, FACS analysis and uptake experiments employing 3-O-methyl-D-(3H)glucose, fluoro-2-deoxy-D-glucose2 [5,6-3H] and 14C-aminoisobutyric acid (AIB). The induction of iodide transport and gene expression were investigated in 125iodide uptake experiments and real-time polymerase chain reaction (PCR). Results: MS-275 induced a concentration- and time-dependent inhibition of proliferation in the thyroid carcinoma cell lines with varying IC50 values. In FRO82-2, SW1736 and FTC133 cells characterized by low, moderate and high sensitivity an up-regulation of p21CIP/WAF1 expression and G1 and/or G2 phase arrest were observed upon MS-275 exposure corresponding to the sensitivity of individual cell lines. In addition, high MS-275 concentrations increased the apoptotic cell fraction of FTC133 and SW1736 cells, whereas resistance to apoptosis and simultaneous up-regulation of Bcl-2 gene expression were observed in FRO82-2 cells. MS-275 treatment also mediated a concentration-dependent decrease of 3H-FDG uptake and an increased 3-O-methyl-D-(3H)glucose uptake in all thyroid carcinoma cell lines after 24 h, an increased uptake of both tracers in FTC133 cells after 48 h, and restored the functional activity of the sodium-iodide symporter in SW1736 and FTC133 cells up to 20- and 45-fold. Conclusion: MS-275 exerts dose-dependent antiproliferative effects including growth arrest, differentiation and apoptosis in some thyroid carcinoma cell lines and might, therefore, be considered for the treatment of anaplastic and non-iodide-concentrating thyroid carcinomas.